Manajemen Strategis Rumah Sakit Berbasis Analisis SWOT untuk Peningkatan Kualitas Pelayanan - Putu Prayoga Tantra; Arie Piet Yeuwun; Purwadhi Purwadhi; Yani Restiani Widjaja (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Increasing competition among hospitals, rising demands for service quality, and changes in healthcare regulations and financing systems require hospitals to implement effective strategic management. One strategic approach widely discussed in the literature is Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. This article aims to examine hospital strategic management based on SWOT analysis as a conceptual framework for improving service quality. The research employs a library research method with a descriptive-analytical approach. Data were obtained from relevant scientific literature, including textbooks, national and international journal articles, and official documents related to strategic management, hospital management, SWOT analysis, and healthcare service quality. Data analysis was conducted through identification, comparison, and synthesis of key concepts and theoretical perspectives. The results indicate that SWOT-based strategic management provides a systematic framework for understanding internal and external conditions of hospitals and supports the formulation of strategic directions oriented toward service quality improvement. The study concludes that SWOT analysis is conceptually relevant as a strategic management tool for hospitals in designing adaptive and sustainable service quality improvement strategies.